2013
DOI: 10.1530/jme-13-0144
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory receptor 51E1 as a novel target for diagnosis in somatostatin receptor-negative lung carcinoids

Abstract: Somatostatin receptors (SSTRs) may be used in lung carcinoids (LCs) for diagnosis and therapy, although additional targets are clearly warranted. This study aimed to investigate whether olfactory receptor 51E1 (OR51E1) may be a potential target for LCs. OR51E1 coding sequence was analyzed in LC cell lines, NCI-H727 and NCI-H720. OR51E1 transcript expression was investigated in LC cell lines and frozen specimens by quantitative real-time PCR. OR51E1, SSTR2, SSTR3, and SSTR5 expression was evaluated by immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 26 publications
(30 reference statements)
1
42
0
Order By: Relevance
“…DR2 is expressed more frequently in ACs than TCs [11]. OR51E1 expression is detected in the majority of SSTR-negative LCs [12], and IGF-1, IGF-1R, CTGF and HIF-1 are expressed in the majority of LCs [13]. In this study, SSR status and that of the aforementioned novel IHC markers was shown to lack any prognostic value for OS and EFS in LCs.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…DR2 is expressed more frequently in ACs than TCs [11]. OR51E1 expression is detected in the majority of SSTR-negative LCs [12], and IGF-1, IGF-1R, CTGF and HIF-1 are expressed in the majority of LCs [13]. In this study, SSR status and that of the aforementioned novel IHC markers was shown to lack any prognostic value for OS and EFS in LCs.…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, the localization of receptor expression was assessed semi-quantitatively based on the classification by Volante et al [19] as follows: Score 1 (S1): pure cytoplasmic immunoreactivity; score 2 (S2): a minority tumour cell population showed membranous immunoreactivity in < 50% of the cell circumference, and score 3 (S3): a majority tumour cell population revealed membranous immunoreactivity in over 50% of the circumference [11, 12, 19]. The intensity of IHC staining for the IGF-1, IGF -1R, CTGF and HIF-1 antibodies were rendered only quantitatively with a 50% cut-off [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although OR51E1 and OR51E2 are ubiquitously expressed in various types of normal and cancerous tissues in humans [2831], they are significantly more abundant in the healthy human prostate [28]. Both GPCRs belong to the largest subgroup in the mammalian genome, the olfactory receptor (OR) multigene family.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a limited number of studies have demonstrated the expression of SSTR subtypes other than SSTR2A in NETs with divergent results, possibly due to differences in the methodology applied [8,9,10,11,12,13,14,15,16,17,18]. Data concerning LCs are even more sparse and inconsistent [15,18,19,20,21,22,23]. Among the five subtypes of SSTRs, SSTR2A is the one most frequently expressed, exhibiting mainly membranous immunostaining, while the other subtypes present mainly cytoplasmic expression [24].…”
Section: Introductionmentioning
confidence: 99%